1996
DOI: 10.1161/01.cir.94.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Only Hibernating Myocardium Invariably Shows Early Recovery After Coronary Revascularization

Abstract: Multivariate analysis identifies hibernating myocardium showing early postrevascularization recovery, as opposed to viable but myolytic myocardium with no early recovery. Postrevascularization recovery can be predicted (combination of low REF and high MET) by noninvasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 28 publications
6
44
0
2
Order By: Relevance
“…These results are qualitatively and quantitatively similar to the results of the present study in which FDG uptake during insulin clamp was the same in hibernating and normal regions. Thus, the finding of homogeneous FDG uptake during insulin clamp by Marinho et al 4 and the present study support a role of regional fibrosis as the explanation for reduced FDG uptake in some clinical studies, as suggested by Shilvalkar et al 10 Increased FDG uptake in the fasting state has been speculated to reflect alterations in myocardial glucose utilization, resulting in altered glucose transporter expression and increased transport capacity. Quantification of mRNA from biopsies of patients with hibernating myocardium has demonstrated induction of the glucose transporter primarily responsible for basal glucose uptake, GLUT1, with no change in the other major myocardial glucose transporter, GLUT4.…”
Section: Fallavollita Heterogeneity Of Fdg In Hibernating Myocardiumsupporting
confidence: 88%
“…These results are qualitatively and quantitatively similar to the results of the present study in which FDG uptake during insulin clamp was the same in hibernating and normal regions. Thus, the finding of homogeneous FDG uptake during insulin clamp by Marinho et al 4 and the present study support a role of regional fibrosis as the explanation for reduced FDG uptake in some clinical studies, as suggested by Shilvalkar et al 10 Increased FDG uptake in the fasting state has been speculated to reflect alterations in myocardial glucose utilization, resulting in altered glucose transporter expression and increased transport capacity. Quantification of mRNA from biopsies of patients with hibernating myocardium has demonstrated induction of the glucose transporter primarily responsible for basal glucose uptake, GLUT1, with no change in the other major myocardial glucose transporter, GLUT4.…”
Section: Fallavollita Heterogeneity Of Fdg In Hibernating Myocardiumsupporting
confidence: 88%
“…Nevertheless, the extent of infarction was trivial, indicating that this is essentially a model of heart failure from viable dysfunctional myocardium arising from chronic episodes of reversible ischemia. In support of reversible dysfunction, our finding of 16.5% connective tissue in the LAD distribution is within the range (11-24%) reported in patients with hibernating myocardium that improved function after revascularization (13,23,32). The results of the present investigation would not be substantively different even if animals with Ͼ1% infarction were excluded.…”
supporting
confidence: 82%
“…Studies described above and many others [123][124][125][126][127][128][129][130][131][132][133][134] support the concept of hibernating myocardium as originally defined. However, one limitation of these clinical studies is that in general they do not track reduced flow and reduced function in a chronic manner, that is, at multiple time points before revascularization.…”
Section: Time Course Of Recovery Of Hibernating Myocardiummentioning
confidence: 83%